Cover Feature: Integrating Catalysis of Methane Decomposition and Electrocatalytic Hydrogen Evolution with Ni/CeO2 for Improved Hydrogen Production Efficiency (ChemSusChem 5/2019). Issue 5 (7th March 2019) - Zhang, Cai; Zhang, Wei; Drewett, Nicholas E.; Wang, Xiyang; Yoo, Seung Jo; Wang, Haoxiang; Deng, Ting; Kim, Jin‐Gyu; Chen, Hong; Huang, Keke; Feng, Shouhua; Zheng, Weitao
Abstract : The Cover Feature shows how hydrogen can be produced through combination of two hydrogen‐producing methods. One is the catalytic decomposition of methane using Ni/CeO2 as catalyst. The solid by‐product Ni/CeO2 /CNT formed in that reaction further acts as electrocatalyst for the hydrogen evolution reaction to produce more hydrogen. This avoids waste, protects the environment and improves the hydrogen‐production efficiency. The clean hydrogen can be used, for example, in proton‐exchange membrane fuel cells. More information can be found in the Full Paper by Zhang et al. onpage 1000 in Issue 5, 2019 (DOI:10.1002/cssc.201802618 ).